2017
DOI: 10.1093/ajh/hpx062
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Body Denervation Markedly Improves Survival in Rats With Hypertensive Heart Failure

Abstract: CBD attenuated the progression of hypertension and worsening of heart failure possibly through sympathoinhibition, and markedly improved survival in a rat model of hypertensive heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…The 24 h urinary samples were collected using metabolic cages, as described previously (Fujii et al, 2017). The 24 h urinary samples were collected using metabolic cages, as described previously (Fujii et al, 2017).…”
Section: Parameters Of Sympathetic Nerve Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The 24 h urinary samples were collected using metabolic cages, as described previously (Fujii et al, 2017). The 24 h urinary samples were collected using metabolic cages, as described previously (Fujii et al, 2017).…”
Section: Parameters Of Sympathetic Nerve Activitymentioning
confidence: 99%
“…The 24 h urinary noradrenaline excretion (U-NA) and plasma noradrenaline concentration (P-NA) were evaluated as indexes of SNA. The 24 h urinary samples were collected using metabolic cages, as described previously (Fujii et al, 2017). The U-NA was measured by high-performance liquid chromatography at a commercial laboratory (SRL, Tokyo, Japan).…”
Section: Parameters Of Sympathetic Nerve Activitymentioning
confidence: 99%
“…2020, 21, 4893 2 of 14 followed by hypertension. The CB is involved in the origin of hypertension and the functional elimination of CB after denervation or ablation prevents the development of hypertension [6][7][8][9][10]. The hyperactivity of the sympathetic system seems to be the link between CB and hypertension [11].…”
Section: Introductionmentioning
confidence: 99%
“…It is currently accepted that chronic intermittent hypoxia (CIH) produces carotid body (CB) sensitization generating an increased input to the brain stem which originates sympathetic hyperactivity, followed by hypertension. The CB is involved in the origin of hypertension and the functional elimination of CB after denervation or ablation prevents the development of hypertension [ 6 , 7 , 8 , 9 , 10 ]. The hyperactivity of the sympathetic system seems to be the link between CB and hypertension [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…CB, located at the bifurcation region of each common carotid artery, is the main peripheral arterial chemoreceptor that senses changes in the levels of oxygen, pH and carbon dioxide in the body 10,11 . A recent study with an animal model of hypertensive HF has shown that CB denervation markedly improved the survival in rats 12 . In fact, single or bilateral removal of CB in clinical studies with >15,000 patients has been reported in the literature with no adverse effects 9 .…”
mentioning
confidence: 99%